Micro Business Productive Infaq Management System at the National Amil Zakat Agency (BAZNAS) Deli Serdang Regency - Adila Husna; Marliyah Marliyah (Jurnal Fokus Manajemen, 2022)
Research with the title “Productive Infaq Management System for Micro-enterprises at BAZNAS Deli Serdang”, aims to find out how the management of productive infaq at BAZNAS Deli Serdang. This study uses a qualitative approach with a type of descriptive method which is a research method that utilizes qualitative data and is described descriptively. The data analysis technique used in this research is a qualitative analysis of the data obtained from the field, either in the form of observations, interviews, and documentation. The results of this study inform that productive infaq managed by BAZNAS Deli Serdang Regency uses a loan system and will be returned with mutually agreed terms.